PENGARUH RISIKO INFLASI TERHADAP TINGKAT RETURN SAHAM DI PT. UNILEVER TAHUN 2015 - 2019 - Saffanah Julita; Gusgana Suria Manda (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
This study aims to determine the impact of inflation in Indonesia on stock returns at PT. Unilever 2015 – 2019. In determining the impact of inflation on stock returns, data that is relevant to the title of the study is needed. This research method is a quantitative research method, the data collection method is a secondary data collection method derived from journals, final assignments, and books that are relevant to this research. Furthermore, for the data analysis method used quantitative descriptive analysis method with stock return data used which means the difference between stock prices in the current period and stock prices in the previous period (capital gain loss). The results of this study indicate that inflation has no effect on the value of stock returns at PT. Unilever in 2015 – 2019.